2022
DOI: 10.3389/fchem.2022.1019166
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in in silico design and characterization of superalkali-based materials and their potential applications: A review

Abstract: In the advancement of novel materials, chemistry plays a vital role in developing the realm where we survive. Superalkalis are a group of clusters/molecules having lower ionization potentials (IPs) than that of the cesium atom (3.89 eV) and thus, show excellent reducing properties. However, the chemical industry and material science both heavily rely on such reducing substances; an in silico approach-based design and characterization of superalkalis have been the focus of ongoing studies in this area along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…To support the outcomes obtained from the above-mentioned inspection, the FMO approach is also applied in terms of some electronic parameters such as HOMO, LUMO, their separation ( E LUMO – E HOMO = E gap ), chemical hardness (η), and electronic chemical potential (μ). Such parameters can be seen in Table . The low E gap value infers high global chemical reactivity, as it is energetically favorable to add electrons to a high-lying LUMO to extract electrons from a low-lying HOMO and therefore to form the activated complex of any potential reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To support the outcomes obtained from the above-mentioned inspection, the FMO approach is also applied in terms of some electronic parameters such as HOMO, LUMO, their separation ( E LUMO – E HOMO = E gap ), chemical hardness (η), and electronic chemical potential (μ). Such parameters can be seen in Table . The low E gap value infers high global chemical reactivity, as it is energetically favorable to add electrons to a high-lying LUMO to extract electrons from a low-lying HOMO and therefore to form the activated complex of any potential reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Superatoms, as one of the most exciting achievements in the development of cluster science territory, have distinct properties and can be considered cluster analogues of individual atoms, where the properties of clusters can be controlled by their size, composition, and even the arrangement of their component atoms. The superatom family constitutes a new dimension of the periodic table and can serve as versatile building motifs of nanomaterials. …”
Section: Introductionmentioning
confidence: 99%
“…From previous studies, it is observed that superalkalis were used to devise novel supersalts, [12][13][14] alkalides, [15,16] electrides, [17,18] superbases [19,20] etc., with unique features. Fascinated by enormous and various applications [21,22] of superalkalis, researchers are continuously trying to model new superalkali species using different central cores and ligands.…”
Section: Introductionmentioning
confidence: 99%